2020
DOI: 10.5187/jast.2020.62.5.668
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the feasibility of Salmonella Typhimurium-specific phage as a novel bio-receptor

Abstract: The purpose of this study was aimed to isolate a Salmonella Typhimurium-specific phage (KFS-ST) from washing water in a poultry processing facility and to investigate the feasibility of the KFS-ST as a novel bio-receptor for the magnetoelastic (ME) biosensor method. KFS-ST against S. Typhimurium was isolated, propagated, and purified using a CsCl-gradient ultracentrifugation. Morphological characteristics of KFS-ST were analyzed using transmission electron microscopy (TEM). Its specificity and efficiency of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Lesions of Salmonella infection appear in the liver and spleen tissues because of bacteremia, which extensively spreads in the organism ( Shao et al, 2013 ; Da Silva et al, 2016 ; Choi et al, 2020 ; Lee et al, 2021 ). The unique vascular system in the liver indicates the sensitivity to inflammation by intestinal-secreted pathogen-associated molecules, as well as danger-associated molecular patterns in hepatocytes ( Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lesions of Salmonella infection appear in the liver and spleen tissues because of bacteremia, which extensively spreads in the organism ( Shao et al, 2013 ; Da Silva et al, 2016 ; Choi et al, 2020 ; Lee et al, 2021 ). The unique vascular system in the liver indicates the sensitivity to inflammation by intestinal-secreted pathogen-associated molecules, as well as danger-associated molecular patterns in hepatocytes ( Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infection, cirrhosis, leukemia, and injury are the main reasons for increasing spleen size ( Gent and Blackie, 2017 ). Hypertrophy is the response of the spleen to intracellular pro-inflammatory cytokine production induced by Salmonella , which results in splenic lesions and hyperplasia ( Oh et al, 2010 ; Choi et al, 2020 ). In agreement, laying hens challenged with S. Typhimurium ( Oh et al, 2010 ; Tian et al, 2018 ) showed a higher relative weight of liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latent period was defined as the time interval between the infection and the release of the first phage from the host. The burst size was calculated as the ratio of the final count of free phage particles after the rise phase to their initial count during the latent period [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…More than 2,600 Salmonella serotypes have been isolated up to date. Among them, nearly 99% of Salmonella serotypes can infect humans or animals [ 1 , 2 ]. It is estimated that Salmonella cause 115 million human infections and 370 thousand deaths annually [ 3 ].…”
Section: Introductionmentioning
confidence: 99%